Research of functional respiratory status in rehabilitation and prevention of the patients with Industrially Conditioned Chronic Bronchitis - T. .. I Grekova; A. P. Sivakov; T. M. Rybina (Doklady Belorusskogo gosudarstvennogo universiteta informatiki i radioèlektroniki, 2019)
The functional respiratory status of patients with industrially conditioned chronic bronchitis was researched. The use of reflexotherapy and magnetotherapy in rehabilitations programs lead to prevention of chronic bronchitis.